AUTHORITATIVE REGULATION AND THE STEM CELL DEBATE - Capps, Benjamin (Bioethics, 2008)
In this paper I argue that liberal democratic communities are justified in regulating the activities of their members because of the inevitable existence of conflicting conceptions of what is considered as morally right. This will often lead to tension and disputes, and in such circumstances, reliance on peaceful or orderly co-existence will not normally suffice. In such pluralistic societies, the boundary between permissible and impermissible activities will be unclear; and this becomes a particular concern in controversial issues which raise specific anxieties and uncertainty. One context that has repeatedly raised issues in this regard is that of biotechnology and, in particular, the recent stem cell debate, on which this paper concentrates. While such developments have the potential to make significant improvements to therapeutic progress, we should also be sceptical because predicting the impact of these developments remains uncertain and complex. For the sake of socio-political stability, it will therefore be necessary to enact and enforce rules which limit these competing claims in public policy but which may not be compatible with what individual moral commitments ideally permit. One way to achieve this is to establish procedural frameworks to resolve potential disputes in the public sphere about what is right, wrong, or permissible conduct. I argue that for one to commit to authoritative regulation, an idea of harm prevention through state intervention is necessary; and that this requires optimum mechanisms of procedure which allow the individual the opportunity to compromise and yet to continue to oppose or fight for changes as demanded by his or her moral position.